Challenges to Achieving a More Inclusive and Sustainable Open Education. Issue 1 (13th December 2021) - Iniesto, Francisco; Tabuenca, Bernardo; Rodrigo, Covadonga; Tovar, Edmundo
This paper showcases relevant initiatives to address inclusive and sustainable development through the objectives of UNESCO's Sustainable Development Goal 4 (SDG4) towards ensuring inclusive and equitable quality education and to promote lifelong learning opportunities for all. These research projects have been possible thanks to initiatives such as the global Open Educational Resources (OER) Graduate Network (GO-GN), a research network that facilitates collaborative research in the area of open education. These types of initiatives empower collaborative research proposals thanks to joint participation in working groups and seminars, which facilitate research collaborations with a clear focus, in this case, on inclusive and sustainable development. In this paper, several challenges on achieving a more inclusive and sustainable Open Education are discussed, such as the need to use accessibility metadata standards to improve the search and sharing of OERs in open repositories, the recommendation to use frameworks like Universal Design for Learning (UDL) to provide inclusive design feedback, and the benefits of action-oriented Massive Open Online Courses (MOOCs) to promote sustainability.